Continued Enteral Feeding Is Beneficial in Hypoglycemic Infants Admitted to Intensive Care for Parenteral Dextrose Therapy. (June 2019) - Alsaleem, Mahdi; Saadeh, Lina; Kumar, Vasantha H. S.; Wilding, Gregory E.; Miller, Lorin; Mathew, Bobby
There is variability in practice among care providers on feeding infants admitted with neonatal hypoglycemia (NH) for parenteral dextrose. We compared clinical outcomes in infants who were fed (NH-Fed) and hypoglycemic infants who were kept nothing per os (NPO) (NH-NPO) at the time of initiation of intravenous (IV) dextrose. We performed a retrospective review of all newborn infants admitted to the neonatal intensive care unit with NH for IV dextrose. Infants were grouped as per the feeding approach at initiation of IV dextrose: NH-Fed or NH-NPO infants. We found that infants in the NH-Fed group had lower maximum glucose infusion rate, less duration of glucose infusion therapy compared with the NH-NPO group, and significantly less number of days of hospital stay compared with the NH-NPO group (5.87 ± 1.4 days vs 4.9 ± 1.4 days, P < .006). In conclusion, feeding infants with hypoglycemia who require IV dextrose offers tangible benefits of shorter duration of parenteral dextrose and shorter length of hospitalization.